The Winchesters. The complete first season [videorecording (DVD)] - Thompson, Robbie (Warner Bros. Entertainment Inc., 2023)
Before Sam and Dean Winchester, there were their parents, John and Mary. Told from the perspective of narrator Dean Winchester, THE WINCHESTERS is the epic, untold love story of how John Winchester met Mary Campbell and put it all on the line to save their love and the entire world. When John returns home from fighting in Vietnam, a mysterious encounter sparks a new mission to trace his father's past. In his journey, he crosses paths with 19-year-old demon hunter Mary, who is also searching for answers after the disappearance of her own father. Together, the two join forces with young hunter-in-training Latika and easygoing hunter Carlos to uncover the hidden truths about both their families. Their investigation leads them to a rare book emporium, whose owner Ada takes an interest to the occult and could provide the missing pieces to their puzzle. But secrets run deep for both the Winchesters and Campbells, and despite the best efforts of John's mother Millie to protect her son from pursuing a dangerous life of demon hunting, John and Mary are both determined to work together to uphold their families' legacies while beginning to form a family of their own.